Tuberculosis Hospital in Aguas de Busot : a personal experience - S. Rubio López; J. Candela Ferri; Sara Miró Batlle; Lara Pozo Cisneros; Eva María Gabaldón Bravo (Universidad de Alicante, 2012)
A special site with an important historical background is analised, considered here as a reflection of the evolution of the nursing profession with the aim of studying and caring for our past, to improve our present and to create a better future.